Patient safety culture in homecare in England: an exploratory study - Le, Thoai Nguyen Anh (2025)
Background: In the health and social care sector, patient safety culture is a key priority. However, research on patient safety culture has extensively focused on hospitals, with very few studies examining safety culture in homecare. Homecare is a crucial part of the health and social care system in England, and there has also been an increase in demand for homecare services due to the aging population and the impact of the COVID-19 pandemic. Consequently, the UK government has made significant efforts and strategic commitments to reform adult social care and highlight the importance of research in homecare.